Perlindungan Data Nasabah Terkait Pemanfaatan Artificial Intelligence dalam Aktifitas Perbankan di Indonesia - Ayunda, Rahmi; Rusdianto, Rusdianto (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The development of information technology resulted in the industrial revolution 4 times. Starting from the 1.0 industrial revolution that occurred in the 18th century until now in the 4.0 industrial revolution that occurred in 2010. The 4.0 Industrial Revolution introduced innovative technology in the industrial world so that the world became acquainted with Artificial Intelligent. The application of Artificial Intelligent in banking activities provides convenience and efficiency to all customers and also the bank. However, technological progress will not be defeated by human greatness. Where hackers can still leak and steal customer data, so regulations related to the application of Artificial Intelligence in banking activities are considered very important. The rise of leaks carried out by hackers is known as cyber crime which can destroy the application of the principle of secrecy in the banking system. This is what then inspires the urgency to protect bank consumers data. This research was conducted using normative Legal research and is intended to provide the benefits derived from the application of AI in banking activities, negative impacts and ways to avoid negative impacts through the formation of new regulations related to the application of Artificial Intelligence in banking activities in Indonesia.